ENERGY CONSUMPTION AND ENVIRONMENTAL PERFORMANCE: A GLOBAL ANALYSIS BASED ON THE 2024 EPI INDEX - ZALIZNYAK, MAKSYM; NETREBSKIY, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the statistical relationship between the average annual per capita electricity consumption and the environmental performance of countries worldwide, as assessed by the Environmental Performance Index (EPI). Additionally, the potential impact of the share of renewable energy sources in national energy balances is analyzed as a modifying factor. The dataset covers 177 countries, with 2024 data collected from open international sources.Methods of descriptive statistics and correlation analysis were applied, along with the development of a logarithmic regression model to identify the nature of the relationship between the variables. The results revealed a moderate positive logarithmic dependence between energy consumption levels and EPI values, indicating a saturating effect: increases in per capita electricity consumption are associated with improvements in environmental performance only up to a certain threshold, after which the effect plateaus. At the same time, significant variability in EPI values among countries with similar consumption levels suggests the role of qualitative aspects of energy policy.The study also includes a clustering of countries by logarithmically scaled per capita electricity consumption and EPI values. The analysis identified typical groups of countries with similar energy consumption and environmental policy profiles, determined Ukraine’s position among them, and highlighted benchmark clusters of states that have achieved high environmental performance under conditions of substantial energy consumption. The clustering results can be used to develop typologies of energy models and to identify potentially relevant practices for the ecological transformation of Ukraine’s energy sector.
Keywords: energy consumption; environmental performance; renewable energy sources; energy policy; environmental sustainability; energy transition